A transmembrane form of annexin XII detected by site-directed spin labeling - Langen, Ralf (The National Academy of Sciences, 1998)
Previous studies of the annexin family of Ca(2+) binding proteins identified a soluble monomer in the absence of Ca(2+) and a trimer adsorbed on the membrane surface in the presence of Ca(2+). On the basis of site-directed spin-labeling studies of annexin XII at low pH, we now report a membrane-inserted form of the protein with a dramatically different structure. The data suggest that upon insertion a continuous transmembrane α-helix is reversibly formed from a helix–loop–helix motif in the solution structure. Other regions with similar membrane-insertion potential were identified in the amino acid sequence, and we propose that the corresponding helices come together to form an aqueous pore that mediates the ion channel activity reported for several annexins.